Inorganic Salts of N-phenylbiguanidium(1+)-Novel Family with Promising Representatives for Nonlinear Optics - Matulková, Irena; Císařová, Ivana; Fridrichová, Michaela; Gyepes, Róbert; Němec, Petr; Kroupa, Jan; Němec, Ivan (International journal of molecular sciences, 2021)
Seven inorganic salts containing N-phenylbiguanide as a prospective organic molecular carrier of nonlinear optical properties were prepared and studied within our research of novel hydrogen-bonded materials for nonlinear optics (NLO). All seven salts, namely N-phenylbiguanidium(1+) nitrate (C2/c), N-phenylbiguanidium(1+) perchlorate (P-1), N-phenylbiguanidium(1+) hydrogen carbonate (P21/c), bis(N-phenylbiguanidium(1+)) sulfate (C2), bis(N-phenylbiguanidium(1+)) hydrogen phosphate sesquihydrate (P-1), bis(N-phenylbiguanidium(1+)) phosphite (P21), and bis(N-phenylbiguanidium(1+)) phosphite dihydrate (P21/n), were characterised by X-ray diffraction (powder and single-crystal X-ray diffraction) and by vibrational spectroscopy (FTIR and Raman). Two salts with non-centrosymmetric crystal structures-bis(N-phenylbiguanidium(1+)) sulfate and bis(N-phenylbiguanidium(1+)) phosphite-were further studied to examine their linear and nonlinear optical properties using experimental and computational methods. As a highly SHG-efficient and phase-matchable material transparent down to 320 nm and thermally stable to 483 K, bis(N-phenylbiguanidium(1+)) sulfate is a promising novel candidate for NLO.
Keywords: Salts; krystalizace; optika a fotonika; soli; Ramanova spektroskopie; Crystallization; krystalografie rentgenová; solid-state DFT; Crystallography, X-Ray; Optics and Photonics; second harmonic generation; spektroskopie infračervená s Fourierovou transformací; N-phenylbiguanidium(1+) cation; Spectrum Analysis, Raman; Spectroscopy, Fourier Transform Infrared; difrakce rentgenového záření; X-Ray Diffraction; vibrational spectra; termogravimetrie; Thermogravimetry; crystal structure